ANALYSIS OF SHARIA BANK SOUNDNESS WITH MULTIPLE LINEAR REGRESSION AND ARIMA-GARCH - Ditra Alif Pradana, Ang
Banks play a very important role in everyday life. However, conventional banks have not been able to cater to all segments of society because their interest-based system contradicts Islamic teachings. Therefore, banks based on Islamic principles, commonly referred to as Sharia Bank, have started to develop in Indonesia. The health of Sharia Bank is an important indicator reflecting the stability and financial performance of the bank, as well as the trust of customers and stakeholders in the Islamic banking system. This study aims to analyze the health of Sharia Bank using the RGEC method (Risk Profile, Good Corporate Governance, Earnings, Capital). This method is employed by taking financial ratios representing each RGEC component. The mathematical model used to determine the health of Islamic banks based on this RGEC method is multiple linear regression. Furthermore, the ARIMA-GARCH model is also used to forecast the financial ratios of Sharia Bank for the next year. Thus, the health of Islamic banks can be forecasted by combining the predicted financial ratios with the developed multiple linear regression model. This study makes an important contribution to understanding the factors that influence the health of Sharia Bank and to developing a more effective forecasting model. These findings are expected to help the management of Sharia Bank in making better strategic decisions and improving their financial performance.